THE LANGUAGE OF SILENCE? GERMAN TRAVELS TO POLAND AFTER 1989 - Ćwiklak, Kornelia (Porównania, 2014)
Can the subaltern speak? – asked Gayatri Spivak. Who gives permission to speak? Who, and if at all, listens? The researcher introduces categories of speaking and listening, supremely useful for researching literature. This article analyses, in this regard, the books of contemporary German literature which are accounts of journeys to Poland. Of importance here is the lack of knowledge of the Polish language among the travellers and its impact on the character, contents and credibility of the coverage. Prolific relevant material for research is provided by the most contemporary German literary traveller who has not been scientifically explored: Petra Reski, Ein Land soweit, 2000; Tina Stroheker, Polnisches Journal. Aufzeichnungen von unterwegs, 1998.